Teacher training and the COVID-19 pandemic: limits and possibilities from the perspective of ICED-UFPA undergraduates (Research, Society and Development, 2021)
This article aims to present an analysis of the objective conditions in the effectiveness of Remote Teaching and the impacts caused on the lives of students in the context of undergraduate courses at the Institute of Educational Sciences (ICED), Federal University of Pará (UFPA), highlighting the limits and possibilities in the access and permanence of students to Remote Education from the perspective of sensitive listening to the student voice, on the access and use of technological and digital resources in the current scenario with the pandemic caused by COVID-19. We opted for exploratory research of the mixed type, using a questionnaire by the Google Forms platform as a data collection instrument, with the target audience of students enrolled in Pedagogy and Physical Education courses, showing predominantly qualitative data that were treated with the technique of thematic analysis. The main results present revealing data regarding: a) Material conditions of access to digital technologies, use of technological equipment and online and offline activities; b) Students' perception of Education in Remote Learning during the pandemic period and c) Conflicts underlying Remote Learning during the pandemic.